Potential applications of halloysite for improved topical drug delivery - Ryan, Catherine (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2007)
The aim of this thesis was to evaluate the potential application of halloysite, an aluminosilicate clay material, for use in topical and transdermal drug delivery. Halloysite is a tubular material, the hollow lumen has been used to control the release of active materials for a range of applications. Price et al. (2001) investigated the release of tetracycline HCI, for use as an anti-fouling agent in marine applications. Salter (2003) investigated the capacity of the tubules to produce sustained release of pesticides. Halloysite is chemically similar to kaolin, which has an established role in pharmaceutical and topical preparations (Handbook of Pharmaceutical Excipients, 2005). Hence it was considered that halloysite might have applications in the area of topical and transdermal drug delivery.
Keywords: Pharmaceutics & Pharmaceutical Technology, Ph.D.; Ph.D. Trinity College Dublin